Reproducibility of corneal, macular and retinal nerve fiber layer thickness measurements using the iVue-100 optical coherence tomography - Mashige, Khathutshelo P (Afr Health Sci, 2017)
PURPOSE: To determine the intra-session and inter-session reproducibility of corneal, macular and retinal nerve fiber layer thickness (RNFL) measurements with the iVue-100 optical coherence tomography in normal eyes. METHODS: These parameters were measured in the right eyes of 50 healthy participants with normal vision. Six scans each for corneal thickness, macular and optic nerve head were taken on one day (intra-session), followed by similar repeated measures on five separate days (inter-session). Reproducibility was computed using intra-class correlation coefficient (ICC), coefficient of variation (COV), and test-retest variability (TRV). RESULTS: For intra-session reproducibility, the ICC, COV and TRV values for mean corneal thickness were 0.924, 2.82%, and 3.06 µm respectively. For the mean macular thickness, they were 0.978, 4.64% and 4.51 µm respectively, while for mean RNFL thickness they were 0.946, 3.19%, and 5.66 µm respectively. Inter-session values for mean corneal thickness were 0.926, 2.65% and 3.48 µm, and 0.916, 2.24% and 2.03 µm for mean macular thickness. For mean RNFL thickness, they were 0.962, 2.21%, and 4.72 µm respectively. CONCLUSION: There was good reproducibility of all measured parameters. However, mean RNFL thickness measurements were the most reproducible, suggesting that this may be the best parameter to use to determine measured changes over time.